Implantación del sistema de contabilidad comercial para la empresa “Cell Market” del cantón Catamayo, provincia de Loja, periodo julio a septiembre del 2014 - Irene Herrera, Sandra Soraya (2015)
The present research: ACCOUNTING SYSTEM IMPLEMENTATION FOR COMMERCIAL COMPANY "CELL MARKET" CANTON CATAMAYO, PROVINCE OF LOJA, PERIOD JULY TO SEPTEMBER 2014, originated from the need to provide the company under study tool basic accounting to control their economic and financial activities, the results allow its owner manager make the best decisions for development and optimal growth of it. Also this research is developed in compliance with a prerequisite to obtaining the Engineer Degree in Accounting and Auditing CPA. The objectives were met as the investigative process was developed; finding concrete solutions to the shortcomings identified in the accounting control which provide the owner make decisions for the development of enterprise solutions. The accounting process is performed with the supporting documentation provided by the owner of the store, from initial inventory of his possessions, opening the journal, ledger, trial balance, worksheet, adjustments, Income Statement, State Financial and Cash Flow Statement situation. Completed thesis work record allowed the importance of the implementation of the Business Accounting CELL MARKET, for the development of their business which allows to have accurate and timely progress of business information so it is recommended to their owns accept the proposal made in this research work as a tool of the accounting process by Permanent Account System, which will organize and control their resources effectively and get more useful